Genetic Polymorphisms of Drug-Metabolizing Enzymes Involved in 6-Mercaptopurine-Induced Myelosuppression in Thai Pediatric Acute Lymphoblastic Leukemia Patients - Khaeso, Kanyarat; Nakkam, Nontaya; Komwilaisak, Patcharee; Wongmast, Piyathida; Chainansamit, Su-on; Dornsena, Areerat; Kanjanawart, Sirimas; Vannaprasaht, Suda; Tassaneeyakul, Wichittra (Journal of Pediatric Genetics, 2020)
Genetic polymorphisms of thiopurine S-methyltransferase (TPMT) and nucleoside diphosphate-linked moiety X-type motif 15 (NUDT15) genes have been proposed as key determinants of 6-mercaptopurine (6-MP)-induced myelosuppression in pediatric acute lymphoblastic leukemia (ALL). In the present study, genotypes of TPMT and NUDT15 were investigated in 178 Thai pediatric patients with ALL by the TaqMan SNP genotyping assay and DNA sequencing. The frequency of TPMT*3C was 0.034. Among NUDT15 variants, NUDT15*3 is the most common variant with the allele frequency of 0.073, whereas those of NUDT15*2, NUDT15*5, and NUDT15*6 variants were 0.022, 0.011, and 0.039. These data suggest that a high proportion of Thai pediatric ALL patients may be at risk of thiopurine-induced myelosuppression.
Keywords: thiopurine methyltransferase; nucleoside diphosphate-linked moiety X-type motif 15; pediatric acute lymphoblastic leukemia